2007
DOI: 10.1371/journal.pntd.0000111
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Leptospirosis and Dengue in Thai Children

Abstract: BackgroundLeptospirosis is an emerging zoonosis that is often under-recognized in children and commonly confused with dengue in tropical settings. An enhanced ability to distinguish leptospirosis from dengue in children would guide clinicians and public health personnel in the appropriate use of limited healthcare resources.Methodology/Principal FindingsWe conducted a prospective, hospital-based, study of children with acute febrile illnesses and dengue in Thailand. Among the children without dengue, we identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
60
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 20 publications
14
60
1
5
Order By: Relevance
“…A study of dengue and leptospirosis among children during an epidemic of the former during in Thailand showed that dengue accounted for 61% of the cases while leptospirosis accounted for 6.0%. 37 While leptospirosis showed two epidemic peaks at ages 6 and 11 years, dengue had a single peak at age 9 years. There was a male predominance in cases of leptospirosis.…”
Section: Discussionmentioning
confidence: 99%
“…A study of dengue and leptospirosis among children during an epidemic of the former during in Thailand showed that dengue accounted for 61% of the cases while leptospirosis accounted for 6.0%. 37 While leptospirosis showed two epidemic peaks at ages 6 and 11 years, dengue had a single peak at age 9 years. There was a male predominance in cases of leptospirosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, leptospirosis is associated with floodwaters following monsoons [11][12][13]. It has also been suggested that temperature and rainfall considerably increase the incidence of DF infections [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Only 31% of confirmed leptospirosis cases were diagnosed as leptospirosis at the time of hospital discharge while another 38% were wrongly diagnosed as dengue fever or dengue hemorrhagic fever (Rafizah et al 2012). A study in Thailand by Libraty et al (2007) also reported that 19% of the children with confirmed leptospirosis were not diagnosed correctly on discharge from hospital. Because the specific treatment differs for both infectious diseases, the availability of antigen-based rapid diagnostic tests is essential to aid the clinicians to make timely and accurate diagnosis as well as to start appropriate treatment regimes, which is even more important in co-infection cases.…”
Section: Discussionmentioning
confidence: 99%
“…Libraty et al (2007) reported that the presence of petechial rash was significantly higher in dengue patients compared to those with leptospirosis. Another study conducted in Brazil by Flannery et al (2001) showed that a greater proportion of patients develop jaundice in leptospirosis infection compared to those with dengue.…”
mentioning
confidence: 98%
See 1 more Smart Citation